Generation Z and Language Politeness: Challenges at SMA Negeri 3 Gowa (Generation and Social Change Perspective): Generasi Z dan Kesantunan Berbahasa: Tantangan di SMA Negeri 3 Gowa" (Perspektif generasi dan perubahan sosial) - Indarwati, Indarwati; Kadir Ismail, Abdul; Absri, Absri (ELOQUENCE : Journal of Foreign Language, 2025)
Background: The linguistic politeness of Generation Z in educational settings has emerged as a significant phenomenon worthy of scholarly examination, particularly in light of the pervasive influence of digital media and shifting communication norms. Purpose: This study employs a qualitative descriptive-analytical approach to examine linguistic politeness challenges among students at SMA Negeri 3 Gowa as representatives of Generation Z. Method: Data were collected through methodological triangulation comprising participant observation, questionnaires administered to 32 students, and analysis of classroom interaction documents, utilizing purposive sampling that accounted for gender diversity and varied social backgrounds. Systematic data analysis was conducted through thematic reduction, matrix presentation, and cross-verification to ensure research validity. Result and Discussion: The findings reveal a prevalent pattern of code-switching between formal and informal registers, with colloquial language dominating peer interactions while more polite forms are maintained in teacher-student communication. The study identifies social media influence and peer group dynamics as determining factors in these politeness paradigm shifts. Conclusion and Implication: This research contributes significantly to the mapping of Generation Z's communication patterns within formal educational contexts, an area that remains understudied. The implications underscore the necessity for implementing context-aware communication education in schools that harmonizes traditional politeness norms with Generation Z's distinctive communication characteristics while preserving their digital identity. These findings provide a foundation for developing responsive language learning models attuned to contemporary communication dynamics.